TRANSFORMASI SOSIAL BUDAYA MASYARAKAT SUKU KOROWAI DALAM KONTEKS MODERNISASI DAN GLOBALISASI - Dian Lestari; Heri Kurnia (FKIP, Universitas Palangka Raya, 2023)
The Korowai tribe is a group of indigenous people who live in remote areas in the province of Papua, Indonesia. The Korowai tribe is known for their wooden houses built in trees to protect themselves from floods and wild animals. The traditions and culture of the Korowai tribe are very unique and unique, such as traditional dances, woodcarving and belief in ancestral spirits. However, modernization and epidemics that are increasingly affecting the region significantly change the life of the Korowai tribe. External influences have changed the lifestyle, diet, and use of technology for the Korowai people. However, they try to maintain their original identity and culture. This study discusses the social and cultural changes of the Korowai tribe in the context of modernization and globalization. The results of the study show that the effects of modernization and globalization affect the daily life of the Korowai tribe with complex changes. Factors influencing these changes are access to the outside world, changes in mindset, foreign cultural influences and infrastructure development. Although these changes had positive impacts such as improving the quality of life, they also had negative impacts in maintaining the original culture and traditions of the Korowai tribe. Therefore efforts to restore the original Korowai culture and traditions are very important through programs that support and develop local culture as well as education about the importance of cultural care. This study recommends further research to understand the impact of changes in social culture on the Korowai tribe and how they respond to these changes.